2002
DOI: 10.1007/s00232-002-1016-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Steric Constraints on the Adsorption of Phenyltin onto the Dipalmitoylphosphatidylcholine Bilayer

Abstract: In this paper, we present studies concerning phenyltin adsorption onto the dipalmitoylphosphatidylcholine bilayer. Phenyltin compounds are known to be biologically active, and their molecular geometry makes it possible to study the effect of steric constraints on their ability to penetrate the model lipid membrane. Using a fluorescence probe as a reporter of the amount of adsorbed compound, we evaluated their affinity to the membrane as a function of the membrane state. The amount of the adsorbed compound was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…Ph 2 SnCl 2 intercalates into the hydrophobic membrane interior, which has little effect on overall membrane properties, whereas Ph 3 SnCl affects the interface at the vicinity of glycerol. 28,41 Such location-activity correlation agrees with experimental evidence and theoretical predictions that the disturbances imposed on the lipid bilayer at the glycerol level affect membrane stability the most. 42 In conclusion, both compounds, Ph 3 SnCl and Ph 2 SnCl 2 , influence the osmotically induced erythrocyte haemolysis, but triphenyltin chloride acts more intensively, reducing erythrocyte plasma membrane mechanical strength.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Ph 2 SnCl 2 intercalates into the hydrophobic membrane interior, which has little effect on overall membrane properties, whereas Ph 3 SnCl affects the interface at the vicinity of glycerol. 28,41 Such location-activity correlation agrees with experimental evidence and theoretical predictions that the disturbances imposed on the lipid bilayer at the glycerol level affect membrane stability the most. 42 In conclusion, both compounds, Ph 3 SnCl and Ph 2 SnCl 2 , influence the osmotically induced erythrocyte haemolysis, but triphenyltin chloride acts more intensively, reducing erythrocyte plasma membrane mechanical strength.…”
Section: Resultssupporting
confidence: 83%
“…This toxicity was then correlated with compound's effect on model lipid bilayer properties. 28 These experiments showed that diphenyltin affects the lipid bilayer hydrophobic region, whereas the triphenyltin disturbs the membrane interphase. In addition, both compounds, being positively charged, change the membrane surface electrostatic potential.…”
Section: Resultsmentioning
confidence: 96%
“…This result agrees with literature data showing that Ph 2 SnCl 2 behaves like a simple detergent, intercalating within the lipid bilayer hydrocarbon chain region. 25 The results of similar experiments for Ph 3 SnCl are presented in Fig. 2.…”
Section: Resultsmentioning
confidence: 80%
“…We have shown previously that phenyltin adsorption depends on phosphatidylcholine membrane organization (gel versus liquid-crystal state) and cholesterol content. 24,25 In addition, the available experimental data and molecular simulations indicate that diphenyltin and triphenyltin adsorb onto the lipid bilayer surface differently. Diphenyltin penetrates deep into the hydrophobic membrane interior, whereas triphenyltin is located within the interface region.…”
Section: Bioorganometallic Chemistrymentioning
confidence: 97%
See 1 more Smart Citation